PERSPEKTIF EKOFEMINISME TENTANG PERLAWANAN PEREMPUAN TERHADAP EKSPLOITASI ALAM DALAM NOVEL TANAH TABU - Sari, Nur Andriana; Ahdiati, Triana; Sugiarto, Bowo (Kafa`ah: Journal of Gender Studies, 2023)
This research-based paper aims to understand and describe the Dani women’s resistance to the exploitation of the Baliem Valley in Papua Province in the novel Tanah Tabu and to find out and explain the relationship between the perspective of ecofeminism and the resistance of Dani women in the novel Tanah Tabu. By using a qualitative method and hermeneutic approach in the framework of the post-structuralist perspective and the constructivism paradigm, the result of the research reveals that the Dani women’s resistance to the exploitation of the Baliem Valley in Papua Province in the novel Tanah Tabu is related and represents an ecofeminism perspective.  Through the texts in the novel Tanah Tabu which has been determined to be the object of research, it can be seen that there is a lot of discrimination, exploitation, and marginalization of Dani women and the Baliem Valley in Papua Province. This triggered the birth of the movement of Dani women to demand discriminatory and exploitative treatment that befalls women and nature.  The issue of subordination to women and nature, which results in the impoverishment of both of them, is a motivating factor for women to fight for the rights of women and nature as represented in literary works.  The characteristics of women’s resistance can be seen from their efforts to make individual claims against exploitation and discrimination carried out by women’s group against the exploitation of nature with the aim of opposing patriarchal-capitalism is a form of representation from the perspective of ecofeminism.